2007
DOI: 10.1007/s10585-007-9126-2
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of the role of endogenous SPARC in mouse models of prostate and breast cancer

Abstract: Secreted protein, acidic and rich in cysteine (SPARC, also known as osteonectin or BM-40) is a glycoprotein component of the extracellular matrix that has been reported to be involved with a variety of cellular processes. Although SPARC expression levels are frequently altered in a variety of tumor types, the exact implications of deregulated SPARC expression--whether it promotes, inhibits or has no effect on tumor progression--have remained unclear. Our recent gene expression analyses have shown that SPARC is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
1
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 44 publications
3
41
1
4
Order By: Relevance
“…These findings are in accord with the reports describing the decreased SPARC expression in primary prostate tumors compared to normal prostates and secondary metastatic sites (Thomas et al, 2000;Wong et al, 2008), and also parallel the reported differential expression of SPARC and its regulator p45-sErb3 (Chen et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These findings are in accord with the reports describing the decreased SPARC expression in primary prostate tumors compared to normal prostates and secondary metastatic sites (Thomas et al, 2000;Wong et al, 2008), and also parallel the reported differential expression of SPARC and its regulator p45-sErb3 (Chen et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…To determine if SPARC exerts similar effects on human prostate cancer, we used human prostate cancer cell lines, DU145, PC3 and LNCaP (with low, absent or detectable endogenous SPARC respectively; Thomas et al, 2000;Wang et al, 2005;Wong et al, 2008) and transiently transfected them with pSPARC. Western blot analysis of cell-cycle regulatory proteins revealed that transient overexpression of pSPARC decreased expression of cyclins A and D1 concomitant with upregulation of p21 Cip and p27 kip ( Figure 2c).…”
Section: Sparc In Prostate Cancer N Said Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the controversy of the pathological role of SPARC in prostate cancer was further affirmed in two separate studies that utilized the SPARC knockout and transgenic adenocarcinoma of the mouse prostate (TRAMP) mouse models. Although Said et al (25) found an inhibitory role of SPARC in tumor and metastatic growth, another study did not identify any role of SPARC in tumor progression and metastasis (49). The discrepancy in the pathological outcome evident in these studies might be due to the differences in genetic background of the mice used in the study.…”
Section: Discussionmentioning
confidence: 91%